Petrophysics : theory and practice of measuring reservoir rock and fluid transport properties - Tiab, Djebbar (Gulf Professional Pub./Elsevier, 2012)
This new edition includes updated case studies, examples and experiments as well as a new chapter on modeling and simulations. It also includes recent advances in wireline logging interpretation methods, effective media models, inversion of resistivity log measurements, dipole acoustic shear and Stoneley wave techniques, Biot-Gassmann models and MRI.
Keywords: Petroleum -- Geology.; Petrology.; elektronické knihy; electronic books